크롬질화처리한 저탄소강의 고분자 전해질 연료전지 분리판으로서의 표면특성 - 최창용(Chang-Yong Choi); 강남현(Nam-Hyun Kang); 남대근(Dae-Geun Nam) (Biuletyn Uniejowski, 2011)
Separator of stack in polymer electrolyte membrane fuel cell (PEMFC) is high cost and heavy. If we make it low cost and lighter, it will have a great ripple. In this study, low carbon steel is used as base metal of separator because the cost of low carbon steel is very cheaper commercial metal material than stainless steels, which is widely used as separator. Low carbon steel has not a good corrosion resistance. In order to improve the corrosion resistance and electrolytic conductivity, low carbon steel needs to be surface treated. We made Chromium electroplated layer of $5μm$, $10μm$ thickness on the surface of low carbon steel and it was nitrided for 2 hours at $1000^{°}C$ in a furnace with 100 torr nitrogen gas pressure. Cross-sectional and surface microstructures of surface treated low carbon steel are investigated using SEM. And crystal structures are investigated by XRD. Interfacial contact resistance and corrosion tests were considered to simulate the internal operating conditions of PEMFC stack. The corrosion test was performed in 0.1 N $H_2SO_4$ + 2 ppm $F^-$ solution at $80^{°}C$. Throughout this research, we try to know that low carbon steel can be replaced stainless steel in separator of PEMFC.